Trust, sustainability, and resilience : management and consumer perspectives - Chen, Kuanchin; Pietrzak, Piotr (Routledge studies in trust research, 2025)
"Trust, Sustainability, and Resilience: Management and Consumer Perspectives offers a comprehensive exploration of the key concepts shaping today's world. This book examines the complex relationship between trust, sustainability, and resilience across various domains, providing insights into their significant implications for both organizations and consumers. Readers will gain a deeper understanding of the theoretical foundations and practical applications of these concepts from both management and consumer perspectives. Structured into two sections: the first section explores management perspectives, highlighting key issues and strategies, while the second section delves into consumer perspectives, examining the role of trust, sustainability, and resilience in shaping consumer behavior and preferences. This book is essential reading for academics, researchers, and practitioners interested in the intersection of trust, sustainability, and resilience. It provides valuable guidance for business leaders and policymakers seeking to integrate these principles into organizational strategies. Consumers and individuals interested in sustainable practices and responsible consumption will also find this book insightful. Whether studying management, environmental stewardship, or social sciences, this book offers a multidisciplinary approach to understanding and implementing trust, sustainability, and resilience principles for a better tomorrow"-- Provided by publisher.